"Modos de fazer" na dança do Brasil: quatro traçados [Cássia Navas] - Repertório, Teatro & Dança (Repertório, 2010)
Fruto de encontro do GT Pesquisa de Dança no Brasil: processos e investigações, da Abrace - Associação Brasileira de Pesquisa e Pós-Graduação em Artes Cênicas, realizado em São Paulo em 2004, o presente texto reúne quatro depoimentos de artistas-pesquisadores-professores da dança do Brasil sobre arte e metodologias de criação e ensino ancoradas em trajetórias individuais. Result of a meeting of the work group Survey of Dance in Brazil: processes and investigations, as a part of Abrace - Brazilian Association for Research and Graduate Studies in Performing Arts, held in São Paulo in 2004, that brings together four testimonials from artists-researchersteachers of dance in Brazil, about art and creating and teaching methodologies anchored in individual trajectories.